2014
DOI: 10.1001/jamapsychiatry.2013.3939
|View full text |Cite
|
Sign up to set email alerts
|

Increased Glutamine in Patients Undergoing Long-term Treatment for Schizophrenia

Abstract: IMPORTANCE The N-methyl-D-aspartic acid receptor hypofunction model of schizophrenia predicts a paradoxical increase in synaptic glutamate release. In vivo measurement of glutamatergic neurotransmission in humans is challenging, but glutamine, the principal metabolite of synaptic glutamate, can be quantified with proton magnetic resonance spectroscopy (1 H-MRS). Although a few studies have measured glutamate, glutamine, and glutamine to glutamate ratio, it is not clear which of these 1 H-MRS indices of glutama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 47 publications
(45 reference statements)
6
66
1
Order By: Relevance
“…4 In our study of the dorsal anterior cingulate, we did find higher totalcholine in SP but no differences in total-creatine. 40 Again, the current study is by far the largest to examine these 2 neurometabolites in schizophrenia.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…4 In our study of the dorsal anterior cingulate, we did find higher totalcholine in SP but no differences in total-creatine. 40 Again, the current study is by far the largest to examine these 2 neurometabolites in schizophrenia.…”
Section: Discussionmentioning
confidence: 91%
“…We previously reported increased glutamine but normal glutamate in the dorsal anterior cingulate. 40 We included 72 medicated SP and 76 HC whom also participated in the present study. Since glutamine involves about one-third to one-fifth of the Glx signal 41 we speculate that our current results of increased Glx may represent primarily elevations in glutamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies provide some evidence of elevated glutamine levels in ACC/mPFC, especially in the early phase of illness. Overall, these studies indicate that glutamate may be unchanged or reduced, especially in more chronic cases, depending on the persistence of symptoms or other factors associated with long-term illness [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 91%
“…However, glutamate and glutamine each participate in several other distinct cell processes and hence may not be closely coupled [28]. MRS studies of glutamate and glutamine concentrations in schizophrenia have been inconsistent, with some studies reporting an increase, others reporting a decrease or no abnormality ( [29][30][31][32][33][34][35], for reviews see [36,37]). One metaanalysis found that glutamate is reduced and glutamine is increased in the ACC in patients with schizophrenia, and both decrease more markedly with age in patients [38].…”
Section: Introductionmentioning
confidence: 99%